Pengaruh Kepercayaan Kepada Pemerintah, Kualitas Pela-yanan Petugas Pajak Dan Diskriminasi Terhadap Kepatu-han Wajib Pajak (Studi Pada Wajib Pajak Umkm Yang Terdaftar Di Kantor Pelayanan Pajak Pratama Malang Selatan) - Abel Nathaniel Bima Arya Kusuma; Pusposari, Devy (Telaah Ilmiah Akuntansi dan Perpajakan, 2023)
This study aims to analyze and examine the effect of trust in government, the service quality of tax officials, and discrimination toward tax compliance. The form of this research is quantitative research. The population in this study are MSME taxpayers registered at the South Malang tax service office. Convenience sampling technique was used with a total of 99 respondents. Data collection techniques were used using a questionnaire that was distributed online and directly by visiting MSMEs in the working area of the South Malang tax service office. Data testing used multiple linear regression analysis using SPSS.25.0. The results showed that trust in government, and service quality of the tax officials has a positive effect on tax compliance, while discrimination has a negative effect on tax compliance. In addition, discrimination is the most influential variable on tax compliance.